ANALISIS DAMPAK DIGITALISASI PADA EFISIENSI OPERASIONAL PERUSAHAAN PERCETAKAN CV. ARZHA PUTRA GEMILANG - Agung Nugraha Iskandar; Rini Indahwati; Muhammad Fauzan Azhmy (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The development of digital technology in the era of Industry 4.0 has had a significant influence on changes in the operational systems of various industrial sectors, including the printing industry. CV. Arzha Putra Gemilang, as one of the printing companies located in Medan City, is required to adapt to the process of digitalization in order to enhance efficiency, effectiveness, and work productivity. This study is motivated by the company’s need to determine the extent to which the implementation of digitalization affects operational efficiency, both in terms of quantitative data and qualitative understanding from field practitioners. This research employs a Mixed Methodology approach, which combines quantitative and qualitative methods. The quantitative approach is used to analyze the influence of the digitalization variable (X) on operational efficiency (Y) through an associative research design, while the qualitative approach is used to deepen the quantitative findings through in-depth interviews and direct observations of digital work processes within the company. The population of this study consists of all 35 employees of CV. Arzha Putra Gemilang, with a census sampling technique, meaning that the entire population was used as the research sample. Quantitative data were collected through questionnaires developed based on the indicators of each research variable, and tested for validity and reliability prior to use. Qualitative data were obtained through semi-structured interviews with company leaders, the head of production, and digital printing operators to gain in-depth insights regarding the impact of digital transformation on efficiency and work culture. Quantitative analysis was conducted using simple linear regression with the assistance of SPSS version 26, while qualitative analysis followed the procedures of data reduction, data display, and conclusion drawing based on the Miles and Huberman model. The results of the quantitative analysis indicate that digitalization has a positive and significant effect on operational efficiency. The correlation coefficient (r) of 0.742 shows a strong relationship between the two variables. The coefficient of determination (R²) value of 0.551 (55.1%) indicates that digitalization contributes 55.1% to the improvement of operational efficiency, while the remaining 44.9% is influenced by other factors beyond this study. The calculated t-value (6.932) is greater than the t-table value (2.015) with a significance level of 0.000 < 0.05, signifying that digitalization has a significant influence on operational efficiency. Meanwhile, the qualitative interview findings reinforce the quantitative results, showing that the implementation of digital systems increases work process speed, reduces production errors, and strengthens the company’s data control systems. However, several challenges remain, such as the limited ability of human resources to master new technologies and the need for regular updates to digital equipment.This study recommends that the company continue to enhance employees’ digital competencies, strengthen information system infrastructure, and cultivate an adaptive work culture to support the sustainability of digital transformation in the future.